The magnitude, determinants and barriers for physical activities among diabetic patients in Qassim area of Saudi Arabia - Aldukhayel, Abdulrhman (International Journal of Advances in Medicine, 2018)
Background: To review the level of physical activity (PA) among adult diabetics and barriers to PA in this population. Methods: This survey was performed in 2017 and enrolled adult diabetics from primary health center of the National Guard in Qassim, Saudi Arabia. International Physical activity questionnaire was used to grade the level of PA. The three intensities of PA (walking, moderate and vigorous exercise), and number of days per week and hours per day were queried for each participant. Metabolic equivalent (MET), a proxy indicator of PA was calculated. Data were analyzed for associations to demographic and diabetes-related factors. Participants were queried on barriers to PA such as time, space, high cost, physical disability, preoccupation with other priorities and languor. Results: We interviewed 395 diabetic patients. The low and moderate levels of PA were noted for 320 (81%) and 75 (19%) participants respectively. None had a high level of PA. Gender (P=0.4), age (P=0.45), body mass index (P=0.66) were not associated to PA. Joint problems (43%), languor (35.2%) and family time (33.9%) were the main barriers that lowered PA. Conclusions: There was a low level of PA among diabetics in Qassim. Barriers to PA should be proactively addressed during patient counseling to improve PA in this population. Counseling direct towards increasing PA may mitigate the physically disabling complications of cardiovascular events among diabetics.